Faktor-Faktor yang Memengaruhi Pendapatan Petani Ikan Nila di Kecamatan Rakit, Kabupaten Banjarnegara - Ariyati, Lutfi; Barokatuminalloh, Barokatuminalloh; Rahajuni, Dijan (Fakultas Ekonomi dan Bisnis Universitas Jenderal Soedirman, 2022)
This study analyzes the effect of the pond area, fish seed, pellet, and participation in aquaculture groups on the income earned by tilapia farmers in Rakit District, Banjarnegara Regency. This study also analyzes which factors have the greatest influence on the income level of tilapia fish farmers. The approach used is a quantitative approach with multiple linear regression analysis model. The population in this study were all tilapia farmers in Rakit District, consisting of 240 farmers with a sample of 71 respondents. The sampling technique used was the snowball sampling method where data were collected through questionnaires and interviews. The results of this study indicate that the variables of pond area, fish seed, and pellet have a positive and significant effect on the income of fish farmers in Rakit District, Banjarnegara Regency, while the participation variable in the aquaculture group has no significant effect. The variable that has the greatest influence on the income of tilapia farmers in Rakit District is pellet. Therefore, it is hoped that farmers can prepare all forms of capital and media used so that the cultivation process can be carried out properly. Having a pond area that is suitable for the number of feeds stocked, and adequate feeding will greatly help the growth of fish to be more optimal.